El programa PowerPoint y su influencia en el aprendizaje de polígonos en el bloque de geometría y medida, en los estudiantes del octavo año de Educación General Básica paralelo “A”, de la Unidad Educativa Fiscomisional Calasanz de la ciudad de Loja, periodo académico 2020-2021. Lineamientos alternativos - Zhiñin Sánchez, Jonathan Joel (2021)
The research work was entitled: The PowerPoint programme and its influence on the learning of polygons in the geometry and measurement block, in students in the eighth year of General Basic Education, parallel "A", of the Calasanz Fiscomisional Educational Unit in the city of Loja, academic period 2020-2021. Alternative guidelines. The general objective was: To determine the incidence of the PowerPoint programme as a didactic tool to improve the learning of polygons in the geometry and measurement block, in the eighth year students of General Basic Education parallel "A", of the Calasanz Fiscomisional Educational Unit of the city of Loja, academic period 2020-2021. The approach used was of a mixed and qualitative-quantitative design, taking into consideration the following methods: descriptive, observational, analytical, deductive, hermeneutic, statistical, scientific; the techniques used were: observation, interview and surveys; also the instruments used were the observation guide, structured interview guide and survey, which were executed based on the theoretical and diagnostic foundations and the design of the alternative guidelines. Among the main results, it was determined that students have difficulties in learning polygons, both in theory and practice, which is the demotivation of each one of them; the population investigated was 48 students and one teacher. It was concluded that the implementation of the PowerPoint programme helps to improve the skills and attention of the students by making games, animations and videos that can be elaborated by the teacher in order to acquire the content in a better way.